Modeling of three-limb three-phase transformer relates to shunt core using in industrial microwave generators with n=2 magnetron per phase - H. Outzguinrimt; M. Chraygane; M. Lahame; R. Oumghar; R. Batit; M. Ferfra (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This paper describes the development and implementation of a digital simulation model of a three-phase transformer relates to shunt core transformer, which used to drive magnetron tubes in the microwave. The focus of this study is based on modeling of a new shell-type of three limbs three-phase transformer. The model uses to feed two magnetrons instead of one magnetron per phase. The proposed model is established on the simultaneous analysis of a duo electromagnetic lumped component equivalent circuit. This latter was implemented in a MATLAB environment under rated conditions. The results obtained from the application of the analytical method are provided results in conformity to the experimental tests in the case of single phase high voltage power supply for one magnetron.